Evaluating the patient’s serum for thyroid stimulating immunoglobulin and Cytotoxic -T-lymphocyte associated protein 4 in Graves hyperthyroidism - Tariq, Alkhansaa; Hayfaa Mahmood Fahad (University of Thi-Qar Journal of Science, 2024)
Graves’ disease (GD) is a common autoimmune disorder that causes an excess of thyroid hormone production. It is mainly due to the production of IgG antibodies that activate the thyrotropin receptor. The aim of this study is to measure the levels of Cytotoxic -T-lymphocyte associated protein 4 and thyroid stimulating immunoglobulin in individuals with GD. It also seeks to establish the connection between thyroid stimulating immunoglobulin and thyroid stimulating hormone (TSH), as well as to assess the predictive value of CTLA4 for Graves’ disease. The study was a case-control investigation conducted at the Alrusafa Center for Diabetes and Endocrinology. It involved a total of 45 people diagnosed with Graves’ illness. The healthy group consisted of 45 individuals who had no previous medical history or clinical indications of hyperthyroidism or any other chronic condition. Blood samples from 90 individuals diagnosed with Graves’ illness and a control group were analyzed to measure the levels of CTLA4, TSI by ELISA. The findings indicated a robust and statistically significant association (P.value<0.01) serum levels of CTLA4 in the patients for Graves’ disease comparing to the control group. The patient samples included 13 men (28.89%) and 32 women (71.11%). There was no significant relationship found between TSI and TSH.